COMPARISON ANTITHYROID EFFECT BETWEEN ORAL ANTIHYPERTHYROIDISM GROUP (METHIMAZOLE AND PROPYLTHIOURACIL) BASED ON MEAN OF THYROID HORMONE LEVEL (FTâ) IN PATIENTS WHO DIAGNOSED HYPERTHYROIDISM IN OUT-PATIENT CLINIC RSUP DR. SARDJITO - , NURUL IZZATI MOHD ZULKIFLI, dr.Mohammad Robikhul Ikhsan, M.Kes., Sp.PD-KEMD. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Since the antithyroid drugs was introduced, propylthiouracil (PTU) and methimazole (MMI) are widely used in treating hyperthyroidism. However less study were conducted to compare which of these antithyroid drug is better in reducing the FTâ level. Objectives: The aim of this study is to compare which of these two oral antithyroid drugs (MMI or PTU) is better in reducing the FTâ level after 30 days therapy. Method: This was a retrospective descriptive study using the data from medical records with code ICD 10. E05: Hyperthyroidism. The survey was conducted in Instalasi Rekam Medis, RSUP Dr. Sardjito, Yogyakarta. The data analysis was done in January 2014 using IBM SPSS 20. Result: The mean difference of FTâ level after 30 days for both MMI and PTU is insignificant (p=0.15). However, MMI shows a greater decrease in reducing FTâ level in the second month of therapy and a greater stability in maintaining FTâ level when reaching the normal range. Meanwhile PTU shows a greater decrease in reducing FTâ level in short course (30 days) therapy. Conclusion: There is no difference in reducing mean difference of FTâ level after 30 days therapy between MMI and PTU group.